(untitled) (Web of Teachers: Inderscience Research, 2025)
The integrity of the human personality is manifested, first of all, in the relationship and interaction of the mental and physical forces of the body. The harmony of the psychophysical forces of the body increases health reserves, creates conditions for creative self-expression in various areas of life. An active and healthy person retains youth for a long time, continues creative activity. No matter how perfect medicine is, it cannot get rid of all diseases. A person is the creator of his own health, for which he needs to fight. From an early age, it is necessary to lead an active lifestyle, be satisfied, engage in physical education and sports, observe the rules of personal hygiene-in a word, in rational ways, achieve real harmony of Health.